การพัฒนาเรซินชนิดโฟโตพอลิเมอไรเซชันสำหรับการพิมพ์สามมิติ - พุทธิดา อักขระชาตะ (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
An interest in 3D printing has been increasing, especially that relies on light-mediated printing which can be used to print liquid resins of varied property depending on types of polymer, photoinitiator and monomer. This research aims to synthesize poly(ethylene glycol) bis-urethane methacrylate (PEG-BUM) as photocrosslinker component that provides flexibility to the printed object. Resins of different formulations were prepared by mixing PEG-BUM with phenyl bis(2,4,6-trimethylbenzyl) phosphine oxide (BAPO) as a photoinitiator, and 2- hydroxyethyl methacrylate (HEMA) as a monomer at different concentrations. The resin was placed into a mold and irradiated with the light of 405 nm at different exposure times to allow polymerization and crosslinking to take place. The weight percentage ratio of PEG-BUM : BAPO : HEMA of 40.00 : 0.75 : 59.25 was found to be the most appropriate formula as it gave homogeneous resin that yielded cured object with high elasticity (up to 541% elongation at break) and strength (Young’s modulus of 0.37295 MPa). A period of 10 second for 405 nm light was certainly long enough to yield harden resin that can be removed from the mold. The optimized resin formulation and the time period obtained from this study will be applied for 3D printing in the future.